2022
DOI: 10.1021/acs.jafc.2c04970
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating Effect of the Total Flavonoids of Morus nigra L. on Prediabetic Mice Based on Regulation of Inflammation and Insulin Sensitization

Abstract: Prediabetes is a critical stage characterized by insulin resistance. Morus nigra L., an edible plant, is widely used in food and nutritive supplements and exhibits various pharmacological activities; however, its therapeutic effects and mechanisms on prediabetes have rarely been reported. In this research, the major components of total flavonoids of M. nigra L. (TFM) were identified, and TFM treatment was found to reduce prediabetes progressing to type 2 diabetes mellitus (T2DM) from 93.75 to 18.75%. The micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Several studies suggested that interventions like exercise, weight loss, dietary modifications, and medication interventions can effectively reduce inflammation and immune responses in individuals with prediabetes. [48][49][50][51] Therefore, MHR might contribute to the progression of prediabetes and its conversion to T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that interventions like exercise, weight loss, dietary modifications, and medication interventions can effectively reduce inflammation and immune responses in individuals with prediabetes. [48][49][50][51] Therefore, MHR might contribute to the progression of prediabetes and its conversion to T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…As an excellent natural product, flavonoids are beneficial to human health and have few adverse side effects. , It is important to recognize that the bioavailability of most dietary flavonoids is low, which is related to factors such as structure, glycosylation, and colonic microbial metabolism . Structural modification and novel delivery systems are common methods to improve the bioavailability and efficacy of flavonoids. For example, phospholipon 90H complex of genistein not only improved the water solubility, dissolution rate, membrane permeation rate, and oral bioavailability of genistein but also significantly enhanced its anti-inflammatory activity .…”
Section: Future Perspectivementioning
confidence: 99%
“…As an excellent natural product, flavonoids are beneficial to human health and have few adverse side effects. 139,140 It is important to recognize that the bioavailability of most dietary flavonoids is low, which is related to factors such as structure, glycosylation, and colonic microbial metabolism. 141 Structural modification and novel delivery systems are common methods to improve the bioavailability and efficacy of flavonoids.…”
Section: Future Perspectivementioning
confidence: 99%
“…In a Caco-2 human colorectal adenocarcinoma/U937 human tissue cell lymphoma cell model, coffee leaf extracts, mainly 5-caffeoylquinic acid (5-CQA), epicatechin, rutin, and mangiferin, exhibited anti-inflammatory effects by significantly inhibiting the production of TNF-α, IL-1β, and IL-8 [83] . Phenolic compounds inhibited the production of BCAAs and IL-8 by inhibiting the expression of Val, Leu, and Ile in the Caco-2 human colorectal adenocarcinoma/U937 human tissue lymphoma cell model.…”
Section: Antioxidant and Anti-inflammatory Mechanismsmentioning
confidence: 99%